Leadership styles preferences of generation Z - seddik boudouda; slimane bellaouar (Journal of Excellence for Economics and Management Research, 2024)
This study attempts to identify the leadership styles preferred by Generation Z, the new entrants into the labor market in the commercial sector. It explores the historical development of leadership theories and generational sequences. On the practical side, the study relies on survey data distributed to 85 employees of the (Printemps) company, which operates in the field of multi-trade. The data was processed using the binary logistic regression technique, with the use of the open-source software (R Programming).The study concluded that transactional leadership is not a preferred style among Generation Z, unlike transformational leadership, which was more significant, followed by servant leadership to a lesser degree. Finally, it recommends that business organizations adopt different leadership styles that consider generational differences in the workplace, taking into account the needs and aspirations of each generation.